Different combinations of monensin and narasin on growth performance, carcass traits, and ruminal fermentation characteristics of finishing beef cattle - Baggio, Marcelo; Gouvêa, Vinícius N.; Barroso, José Paulo R.; Miszura, Alexandre A.; Limede, Arnaldo C.; Soares, Letícia C. B.; Ferraz, Marcos Vinicius C.; Vicente, Ana Carolina S.; Ferreira, Evandro M.; Marques, Rodrigo S.; Pires, Alexandre V. (Frontiers in Veterinary Science, 2023)
The objective was to evaluate the effects of different combinations of monensin and narasin for finishing cattle. In Exp. 1, forty rumen-cannulated Nellore steers (initial body weight [BW] = 231 ± 3.64 kg) were blocked by initial BW and assigned to one of the five treatments: Control (CON): no feed additive in the basal diet during the entire feeding period; Sodium monensin (MM) at 25 mg/kg dry matter (DM) during the entire feeding period (adaptation [days 1 to 21] and finishing [days 22 to 42] periods); Narasin (NN) at 13 mg/kg DM during the entire feeding period (adaptation and finishing periods); Sodium monensin at 25 mg/kg DM during the adaptation period and narasin at 13 mg/kg DM during the finishing period (MN); and narasin at 13 mg/kg DM during the adaptation period and sodium monensin at 25 mg/kg DM during the finishing period (NM). Steers fed MM had lower dry matter intake (DMI) during the adaptation period compared to NM (P = 0.02), but not compared to CON, MM, MN, or NN (P ≥ 0.12). No differences in DMI were observed among the treatments during the finishing (P = 0.45) or the total feeding period (P = 0.15). Treatments did not affect the nutrient intake (P ≥ 0.51) or the total apparent digestibility of nutrients (P ≥ 0.22). In Exp. 2, one hundred and twenty Nellore bulls (initial BW = 425 ± 5.4 kg) were used to evaluate the effects of the same treatments of Exp. 1 on growth performance and carcass characteristics of finishing feedlot cattle. Steers fed NM had greater DMI during the adaptation period compared to CON, MM, and MN (P ≤ 0.03), but no differences were observed between NM and NN (P = 0.66) or between CON, MM, and NN (P ≥ 0.11). No other differences between treatments were observed (P ≥ 12). Feeding narasin at 13 mg/kg DM during the adaptation period increases the DMI compared to monensin at 25 mg/kg DM, but the feed additives evaluated herein did not affect total tract apparent digestibility of nutrients, growth performance, or carcass characteristics of finishing cattle.